2006
DOI: 10.1128/mcb.00723-06
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interplay between Histone Demethylase and Deacetylase Enzymes

Abstract: Histone deacetylase (HDAC) inhibitors are a promising class of anticancer agents for the treatment of solid and hematological malignancies. The precise mechanism by which HDAC inhibitors mediate their effects on tumor cell growth, differentiation, and/or apoptosis is the subject of intense research. Previously we described a family of multiprotein complexes that contain histone deacetylase 1/2 (HDAC1/2) and the histone demethylase BHC110 (LSD1). Here we show that HDAC inhibitors diminish histone H3 lysine 4 (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
200
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(225 citation statements)
references
References 37 publications
23
200
0
2
Order By: Relevance
“…2d,e). Next, we addressed whether the demethylase activity of Lsd1 is required for directing TSC fate by ectopic expression of a catalytic inactive mutant of Lsd1 (Lsd1 Mut ) 30 . Ectopic expression of the Lsd1 mutant protein in Lsd1 À / À TSCs does not alter the transcription of stem cellassociated genes such as Eomes (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2d,e). Next, we addressed whether the demethylase activity of Lsd1 is required for directing TSC fate by ectopic expression of a catalytic inactive mutant of Lsd1 (Lsd1 Mut ) 30 . Ectopic expression of the Lsd1 mutant protein in Lsd1 À / À TSCs does not alter the transcription of stem cellassociated genes such as Eomes (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although cross talk between histone deacetylation and demethylation has previously been suggested to modulate gene expression in mammalian cells (Shi et al, 2005;Lee et al, 2006), the direct association of a HDAC with a histone demethylase has not been reported. In this study, we found that HDA6 physically associates with FLD in vitro and in vivo, indicating that these two proteins act in the same protein complex.…”
mentioning
confidence: 99%
“…The peripheral zone of the nucleus is the area that has been implicated in the regulation of gene expression, especially gene silencing (Deniaud and Bickmore, 2009). The mammalian histone demethylase, LSD1, is an integral component of histone deacetylase corepressor complexes, in which HDACs and LSD1 may cooperate to remove activating acetyl and methyl histone modifications (Shi et al, 2005;Lee et al, 2006). HDAC inhibitors can diminish histone demethylation activity, whereas the abrogation of LSD1 activity by mutations can decrease deacetylation activity (Lee et al, 2006), suggesting that the enzymatic activities of HDACs and LSD1 are closely linked.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…LSD1: Lysine-specific demethylase 1 (LSD1) demethylates histone 3 at lysine residues 4 and 9, leading to silencing of enhancers (Shi et al, 2004). LSD1 functionally interacts with other chromatinmodifying enzymes, including histone deacetylases that remove acetyl groups from histone 3 at lysine residue 27 (Lee et al, 2006).…”
Section: Vp64mentioning
confidence: 99%